2016
DOI: 10.1136/medethics-2016-103866
|View full text |Cite
|
Sign up to set email alerts
|

Patients' views of consent in clinical trials for acute myocardial infarction: impact of trial design

Abstract: These findings suggest that patients prefer prospective involvement in enrolment decisions to enrolment without consent across trial types. However, their desire to participate was affected by trial type. There is a need to develop and evaluate context-sensitive approaches to consent in AMI trials that account for both the acuity of the situation and trial characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…However, the level of acceptability varied associated with the nature and purpose of the study (see Additional file 3: Table S8 reporting the studies' key findings, and suppl. 9additional reporting [130][131][132][133]). Most studies (59.1%) were conducted with public members (including researchers, healthy populations, IRBs) and used observational designs (e.g.…”
Section: Public Attitudes On Enrolling Adults Lacking Capacity In Resmentioning
confidence: 99%
“…However, the level of acceptability varied associated with the nature and purpose of the study (see Additional file 3: Table S8 reporting the studies' key findings, and suppl. 9additional reporting [130][131][132][133]). Most studies (59.1%) were conducted with public members (including researchers, healthy populations, IRBs) and used observational designs (e.g.…”
Section: Public Attitudes On Enrolling Adults Lacking Capacity In Resmentioning
confidence: 99%
“…Other studies [14,22] have demonstrated that patients' confidence in healthcare professionals is generally strong, and this might be an explanation for the patients' satisfaction and trust in verbal information in the acute phase of an AMI. Fig.…”
Section: Informationmentioning
confidence: 97%
“…The current common practice in AMI trials is to obtain prospective, most often written IC [12], but this has recently been debated [3,[12][13][14][15]. In the HEAT-PPCI trial, comparing bivalirudin and heparin, the ethics committee in the UK approved a delayed IC process [16].…”
Section: Introductionmentioning
confidence: 99%
“…While prior data suggest a general preference for consent across various types of trials in MI, future work examining the impact of study features on specific consent preferences would be useful. 15 Third, the response rate limits generalizability to some extent, but respondents were similar demographically to the general population. The experimental design also adds internal validity.…”
Section: Limitationsmentioning
confidence: 99%
“…6,14 Second, available data suggest patients generally prefer to be asked permission prior to research enrollment, even for acute conditions. 12–15 Third, surveys of the public have suggested a preference for prospective consent in pragmatic trials in less acute settings, even when treatment-related risks are low and treatments are similar. 16,17 Fourth, failure to obtain research consent could potentially undermine public trust.…”
Section: Introductionmentioning
confidence: 99%